Orographic and convective gravity waves above the Alps and Andes mountains during GPS radio occultation events – a case study - Hierro, Rodrigo Federico (2017)
The significant distortions introduced in the measured atmospheric gravity wavelengths by soundings other than in vertical and horizontal directions, are discussed as a function of elevation angle of the sounding path and the gravity waves aspect ratio. Under- or overestimation of real vertical wavelengths during the measurement process depends basically on the value of these two parameters. The consequences of these distortions on the calculation of the energy and vertical flux of horizontal momentum are analyzed and discussed in the context of two experimental limb satellite setups: GPS-LEO radio occultations and TIMED/SABER measurements. Possible discrepancies previously found between the momentum flux calculated from satellite temperature profiles, on site and from model simulations, may, to a certain degree, be attributed to these distortions. A recalculation of previous momentum flux climatologies based on these considerations seems to be a difficult goal.